Primary Appendix Lymphoma: Case Report and Review of the Literature - Ardicli, Burak; Karaman, Ayse; Yesil, Sule; Arda, Nilufer; Sahin, Gurses; Ozguner, Ismet Faruk (Acta Medica, 2018)
Appendectomy is the most frequent emergent surgical procedure in childhood. Carcinomas are the most frequent neoplasms in the appendix, other neoplasms such as carcinoid tumors and lymphomas may seen less frequently. Primary tumors of the appendix are very rare. We report a patient presented with acute appendicitis diagnosed with B-cell lymphoma after pathological examination.